Jasmonate-regulated root growth inhibition and root hair elongation. (8th November 2022) - Han, Xiao; Kui, Mengyi; He, Kunrong; Yang, Milian; Du, Jiancan; Jiang, Yanjuan; Hu, Yanru
Abstract: The phytohormone jasmonate is an essential endogenous signal in the regulation of multiple plant processes for environmental adaptation, such as primary root growth inhibition and root hair elongation. Perception of environmental stresses promotes the accumulation of jasmonate, which is sensed by the CORONATINE INSENSITIVE1 (COI1)–JASMONATE ZIM-DOMAIN (JAZ) co-receptor, triggering the degradation of JAZ repressors and induction of transcriptional reprogramming. The basic helix–loop–helix (bHLH) subgroup IIIe transcription factors MYC2, MYC3, and MYC4 are the most extensively characterized JAZ-binding factors and together stimulate jasmonate-signaled primary root growth inhibition. Conversely, the bHLH subgroup IIId transcription factors (i.e. bHLH3 and bHLH17) physically associate with JAZ proteins and suppress jasmonate-induced root growth inhibition. For root hair development, JAZ proteins interact with and inhibit ROOT HAIR DEFECTIVE 6 (RHD6) and RHD6 LIKE1 (RSL1) transcription factors to modulate jasmonate-enhanced root hair elongation. Moreover, jasmonate also interacts with other signaling pathways (such as ethylene and auxin) to regulate primary root growth and/or root hair elongation. Here, we review recent progress into jasmonate-mediated primary root growth and root hair development. Abstract : JAZ proteins interact with and suppress bHLH subgroup IIIe and IIId transcription factors to regulate jasmonate-induced root growth inhibition, and repress RHD6 and RSL1 to modulate jasmonate-enhanced root hair elongation.